The Influence of Halal Literacy, Religiosity, Influencer Marketing, and Price on Halal Cosmetic Decisions - Nur Aini, Dwi Putri Ayu; Hanifah, Luluk (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The rapid growth of Indonesia’s halal cosmetic sector is driven by increasing halal awareness, religiosity, digital marketing, and fair pricing. However, empirical studies integrating behavioral factors with the Maqashid Shariah framework remain limited, particularly among Generation Z consumers. This study employs a mixed-method sequential explanatory design, beginning with a quantitative survey of 100 Gen Z consumers in East Java, followed by qualitative analysis to interpret the results through Islamic economic law and Maqashid Shariah principles. Quantitative data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS 26. The qualitative stage contextualizes findings within hifdz al-dīn, hifdz al-nafs, hifdz al-‘aql, hifdz al-nasl, and hifdz al-māl. The regression results show that Religiosity and Price have a positive and significant effect on purchasing decisions, while Halal Literacy and Influencer Marketing have positive but insignificant effects. Simultaneously, all variables significantly influence purchasing decisions, with an Adjusted R² of 0.792. Price is the most dominant predictor, followed by Religiosity. The findings indicate that Gen Z’s halal cosmetic choices are shaped by economic considerations and religious commitment consistent with Maqashid Shariah. Ethical pricing, credible influencers, and strengthened halal literacy enhance rational, safe, and sharia-compliant consumption. This study contributes to Islamic Economic Law by demonstrating how behavioral and normative factors jointly shape halal purchasing behavior and suggests strengthening halal literacy, BPJPH oversight, and DSN-MUI certification governance for a sustainable halal industry.Keywords: Halal Literacy; Religiosity; Influencer Marketing; Price; Purchasing Decision